Analisis Kesulitan Dalam Menerjemahkan Qira’ah Pada Pembelajaran Muthala’ah - Hastang, Hastang; Jamil, Husnaini; Ahmadi, Maswan; Maghfirah, Maghfirah (IAIN Bone, 2025)
This study aims to determine how difficult it is for students to translate Qiraah in Muthala'ah learning. This study is a descriptive qualitative study. The subjects of the study were 4th semester students in the 2025/2026 academic year. Data collection was carried out through documentation and performance with performance guidelines and documents. The data collected from the results of this study will be analyzed using qualitative data analysis.The results of the study show that the difficulties faced by students in translating Qira'ah in Muthala'ah learning can be seen in several aspects, namely 1) Vocabulary. 2) Phrases, 3) Sentence structure, 4) Understanding, and 5) Socio-cultural.